2023
DOI: 10.1002/cac2.12459
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine metabolic microenvironment drives M2 macrophage polarization to mediate trastuzumab resistance in HER2‐positive gastric cancer

Abstract: Background Trastuzumab is a first‐line targeted therapy for human epidermal growth factor receptor‐2 (HER2)‐positive gastric cancer. However, the inevitable occurrence of acquired trastuzumab resistance limits the drug benefit, and there is currently no effective reversal measure. Existing researches on the mechanism of trastuzumab resistance mainly focused on tumor cells themselves, while the understanding of the mechanisms of environment‐mediated drug resistance is relatively lacking. This study aimed to fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“… 35 M2 macrophages can also produce anti‐inflammatory and apoptosis‐inhibiting factors, suppressing the activity of immune cells and weakening the presentation of tumour antigens and the immune system's killing effect on tumours. 36 M2 macrophages can secrete matrix metalloproteinases and detachment‐related factors that promote tumour cell invasion and metastasis by disrupting the basement membrane, as well as enhancing tumour cell invasion and metastatic abilities through interactions with gastric adenocarcinoma cells, releasing cytokines and chemokines. 37 , 38 Anti‐inflammatory cytokines and immune‐suppressive molecules produced during the polarization of M2 macrophages, such as anti‐inflammatory cytokine IL‐10 and anti‐inflammatory cytokine TGF‐β, suppress the activity of immune cells such as T cells and natural killer cells, weakening their attack against tumour cells and promoting immune escape of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“… 35 M2 macrophages can also produce anti‐inflammatory and apoptosis‐inhibiting factors, suppressing the activity of immune cells and weakening the presentation of tumour antigens and the immune system's killing effect on tumours. 36 M2 macrophages can secrete matrix metalloproteinases and detachment‐related factors that promote tumour cell invasion and metastasis by disrupting the basement membrane, as well as enhancing tumour cell invasion and metastatic abilities through interactions with gastric adenocarcinoma cells, releasing cytokines and chemokines. 37 , 38 Anti‐inflammatory cytokines and immune‐suppressive molecules produced during the polarization of M2 macrophages, such as anti‐inflammatory cytokine IL‐10 and anti‐inflammatory cytokine TGF‐β, suppress the activity of immune cells such as T cells and natural killer cells, weakening their attack against tumour cells and promoting immune escape of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…found that patients with high infiltration of macrophages (CD68) were often related to poor response to neoadjuvant chemotherapy in a 103 sample cohort 41 . Meanwhile, high infiltration of M2 TAMs (CD206) was usually forecasted as resistant to trastuzumab therapy in patients with HER2‐positive GC 71 . Sun et al.…”
Section: The Relationship Between Tams and The Prognosis Of Patients ...mentioning
confidence: 99%
“…As a key communication medium in the TME, 62 EVs exert a critical function in inducing the polarisation of TAMs 63 . Accumulative research has reported that EVs containing microRNAs, circular RNAs, long non‐coding RNAs (lncRNAs) or proteins derived from GC cells regulated the polarisation of TAMs after the internalisation by macrophages 52,64–71 . Notably, natural compounds extracted from plants, such as flavokawain B, sophoridine, diosmetin, elian granules and betulinic acid, were found to enhance the polarisation of M1 TAMs 72–76 .…”
Section: The Role and Mechanism Of Tams In Gcmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al 40 reported that HCG18 can promote cetuximab resistance in CRC cells through the miR‐20b‐5p/PD‐L1 axis. In the multidrug resistance of cancer, upregulation of FOXO1 expression and M2 macrophage polarization can enhance the drug resistance of tumor cells 82–85 . Overexpression of miR‐365a‐3p inhibits multidrug resistance in CRC cells 54 .…”
Section: Hcg18 In Human Diseasementioning
confidence: 99%